A Genetic Polymorphism in the WDR72 Gene is Associated With Calcium Nephrolithiasis in the Chinese Han Population - Wang, Lujia; Zhou, Zijian; Yang, Yuanyuan; Gao, Peng; Lin, Xiaoling; Wu, Zhong (Frontiers in Genetics, 2022)
A previous genome-wide association study (GWAS) reported several novel loci for nephrolithiasis in British and Japanese population, some of which were predicted to influence CaSR signaling. In this study, we aimed to evaluate the association of these loci with calcium nephrolithiasis in Chinese Han population. We performed a case-control association analysis involving 691 patients with calcium nephrolithiasis and 1008 control subjects. We were able to genotype a total of 17 single-nucleotide polymorphisms (SNPs), which were previously reported to be significantly associated with nephrolithiasis in GWAS. rs578595 at WDR72 was significantly associated with calcium nephrolithiasis in Chinese Han population (P=4.29×10-6, OR=0.617). Moreover, rs12654812 at SLC34A1 (P=0.04273, OR=1.17), rs12539707 at HIBADH (P=0.01787, OR=0.7341), rs1037271 at DGKH (P=0.00964, OR=0.8284) and rs12626330 at CLDN14 (P=0.00795, OR=1.213) indicated suggestive associations with calcium nephrolithiasis. Our results elucidated the significance of genetic variation at WDR72, DGKH, CLDN14, SLC34A1 and HIBADH in Chinese patients with nephrolithiasis. Since polymorphisms of WDR72, DGKH and CLDN14 are predicted to influence in CaSR signaling, our results emphasized the role of abnormal calcium homeostasis in calcium nephrolithiasis.